A randomized clinical trial of freeze-dried amniotic membrane transplantation and conjunctival-limbal graft for pterygium excision and evaluation of conjunctival inflammation marker in tears (Medical Journal of Indonesia, 2020)
BACKGROUND Minimizing inflammation on the ocular surface after pterygium surgery is essential to prevent recurrence. Currently, limited data are available for the comparison between freeze-dried amniotic membrane (FD-AM) and conjunctival–limbal graft (CLG). Therefore, this study aimed to assess conjunctival inflammation and the interleukin (IL)-6 levels in tears after pterygium excision between both techniques. METHODS This prospective, single-blinded, randomized clinical trial included 26 eyes of 26 patients with primary or recurrent pterygium and who were indicated for pterygium surgery at Cipto Mangunkusumo Hospital, Indonesia from October 2017 until February 2018. The patients were scheduled for pterygium excision with FD-AM or CLG based on block randomization. Conjunctival inflammation and the level of IL-6 in tears were measured on day-7 and -28 after surgery. RESULTS The 26 eyes (13 in each group) were subjected to a complete 1-month follow-up period. Day-7 after the surgery, severe inflammation occurred in 4/13 (31%) eyes having FD-AM and 8/13 eyes (62%) having CLG (p = 0.59). The IL-6 tear level increased similarly in FD-AM (22.85 pg/ml) and CLG (23.51 pg/ml) in (p = 0.78). No severe adverse events occurred. CONCLUSIONS Pterygium excision using FD-AM yield a milder inflammation than CLG on day-7 and -28 after surgery. The tear IL-6 levels similarly increased on day-7.